Conceptualising Space in Transnational Migration Studies. A Critical Perspective - Riaño, Yvonne (Bonn: Bonn University press. V&R Academic, 2017)
This paper argues that space is a crucial dimension of study when studying migration and mobility. However, the conceptualisation of space, and how people “produce” transnational social space through their everyday cross-border actions, remain insufficiently explored in studies of transnational migration. After critically reviewing the literature, the paper raises the question of what could be a conceptually adequate and empirically practicable approach to examine space in studies of transnational migration and mobility. It proposes a conceptual model comprising three interrelated dimensions of analysis: materiality, social practice, and meaning.